Evaluating the Impact of Coronary Artery Calcium on Cardiovascular Risk Stratification in an Indian Cohort - Shiladitya Kumar Singh; Priyanka Singh (Student's Journal of Health Research Africa, 2024)
Background: Coronary artery calcium (CAC) scoring has emerged as a significant marker for cardiovascular risk assessment, but its utility in an Indian cohort has not been extensively studied. This study aimed to evaluate the impact of CAC on cardiovascular risk stratification in an Indian cohort using WHO ISH and ACC/AHA risk calculators. Methods: A cross-sectional observational study was conducted on 80 participants aged 30-75 years with at least one cardiovascular risk factor and no known atherosclerotic cardiovascular disease. Detailed history, clinical examinations, biochemical tests, and 64-slice coronary CT angiograms were performed. Two risk calculators (WHO ISH and ACC/AHA) were used to estimate 10-year cardiovascular risk. Participants were classified based on CAC scores, and statistical analysis was carried out to evaluate the association between CAC scores and CV risk factors. Results: The study found that 25% of participants had no CAC, 50% had moderate CAD, and 25% had obstructive CAD. Higher CAC scores significantly correlated with age (r = 0.45, p < 0.001), BMI (r = 0.30, p = 0.005), hypertension (r = 0.40, p < 0.001), diabetes (r = 0.35, p = 0.002), and lipid profiles. Participants with higher CAC scores were more likely to be categorized as high risk for 10-year CV events. Among those with obstructive CAD, 75% were classified as high risk by WHO ISH and ACC/AHA calculators, compared to 0% in the low-risk category (p < 0.001 for both). Conclusion: CAC scoring enhances cardiovascular risk stratification in an Indian cohort, identifying high-risk individuals more accurately than traditional risk calculators alone. Recommendations: CAC scoring should be considered in routine cardiovascular risk assessment, particularly for individuals with moderate risk by traditional methods, to guide more aggressive preventive strategies.